Assessment of Land Use and Land Cover Change: A Comparative Study of Tribal and non-Tribal District in Gujarat (International Journal of Scientific Research in Science and Technology, 2025)
To support development activities in a given area, it is necessary to have a thorough grasp of the land use and land cover because these elements offer important information about the topography of that area. By analyzing satellite imagery using remote sensing and Geographic Information System (GIS) techniques, this study explores the land use, land cover, and changes in the districts of Dahod and Gandhinagar. The study has used a supervised classification technique to assess the changes in land use and land cover between 2016 and 2022. In the Gandhinagar district, as more people purchase property for residential building, urbanization is increasing, leading to a decrease in agricultural and wooded regions and an increase in wasteland. In contrast, the majority of the land in the Dahod district is unsuited for agriculture due to its mountainous and flat environment. There is hence an abundance of wasteland in the Dahod district. There are currently attempts to encourage farming on these hills and plateaus in Dahod district, which will reduce the amount of wasteland.